The relationship between smile attractiveness and aesthetics parameters of patients with lateral agenesis treated with tooth recontouring or implants [Erratum] - De-Marchi LM; Pini NI; Pascotto RC (Dove Medical Press, 2013)
De-Marchi LM, Pini NI, Pascotto RC. Clinical, Cosmetic and Investigational Dentistry. 2012;4:43–49.The title of the paper named in reference 26 was shown as "Orthodontic considerations for rehabilitation of patients with hypodontia using endosseous implants." The correct title is "Orthodontic considerations in restorative management of hypodontia patients with endosseous implants."Read the original article